MEDIA SOSIAL DAN EVANGELISASI DIGITAL UNTUK KATEKIS: STRATEGI MEMANFAATKAN PLATFORM DIGITAL UNTUK MEMBAGIKAN AJARAN KATOLIK KEPADA GENERASI DIGITAL - Anselmus Yata Mones (Bahasa Indonesia, 2026)
The development of digital technology and social media has opened new opportunities for the Catholic Church to spread its teachings to the digital generation. Digital evangelization has become important in this modern context, especially to reach those who may not be involved in traditional religious practices. The method used in this research is a literature review, where the researcher collect various articles to explain the topic. The research results show that the effective implementation of digital evangelization requires an improvement in the quality of presenting the Church's core values and ease of acceptance by the target audience. Through the right strategies, social media and digital platforms can become powerful tools for spreading Catholic teachings to the digital generation. Therefore, it is important to educate catechists and the faithful about the ethical use of social media and digital technology to ensure that the message of evangelization is conveyed in an effective and meaningful way.